O idoso vítima de violência : desafios do sistema de saúde para o enfrentamento do fenômeno - Freitas, Cibelly Aliny Siqueira Lima (2011)
In Brazil the representativity of the age groups in the total population in 2010 is lower than that observed in 2000 for all groups aged up to 25 years, whereas the other age groups increased their participation in the last decade. This demonstrates the widening at the top of the age pyramid, where there was a participation increase relative to the population aged 65 years of more, which was 4.8% in 1991, rising to 5.9% in 2000 and reaching 7.4% in 2010 (IBGE, 2011). Demographic data shows the need for urgent changes that result in the execution of public policies for elderly care, especially those victims of violence, as this aggravation has been highlighted in the health and sickness process of this population. Facing this reality, we developed this survey with the objective of understanding the health care model of the elderly victim of violence in the Health System of Sobral, Ceara, considering the principle of integrality. For which, we performed a comprehensive study, of qualitative nature with professionals who represent the management and care segments in the health system of Sobral, Ceara, Brazil, composed of six coordinators from collegiate management, six nurses and five community health agents. The information was collected in the period from October 2010 to March 2011 by means the Hermeneutic Dialectic Circle (HDC) technique adapted by Oliveira (2007) and submitted to speech analysis. The study incorporated the principles of Bioethics according to Resolution 196/96 from the National Health Council. The results revealed that the health system in Sobral presents a care model to the elderly victim of violence that acknowledges the phenomenon and recognizes it as a reality that is intensified in the city of Sobral, Ceara, presenting the most diverse forms of ill-treatment. This care appears neglected, in the speeches from the deponents on why the system does not attend the elderly in its totality, denouncing difficulties in the operance on the Integrality principle. Considering the situational context of the elderly that suffer violence in Sobral, the health care model defended in the speeches from professionals and the directives of the Elderly Statute, National Health Policy of the Elderly and Health Pact, we observed that the policies studied are only contemplated partially, leaving, the city, a challenging task to lay the way, in the sense of providing effective and efficacious answers to the demands and needs for the health of the elderly population.